Software of aircraft static stability and performance - 435639 Yong, Kok Wei (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Engineering (Mechanical - Aeronautical)) - Universiti Teknologi Malaysia, 2001